To rewrite the expression in standard form, we need to add up the terms:
(2.49 x 10^-2) + (3.15 x 10^-3) + (1.02 x 10^2)
First, let's rewrite each term in standard form:
2.49 x 10^-2 = 0.0249
3.15 x 10^-3 = 0.00315
1.02 x 10^2 = 102
Now we can add up the terms:
0.0249 + 0.00315 + 102 = 102.02705
Finally, we can write the expression in standard form:
(2.49 x 10^-2) + (3.15 x 10^-3) + (1.02 x 10^2) = 102.02705
((2.49 x 10^-2) + (3.15 x 10^-3) + (1.02 x 10^2)
What is the expression in stander form?
1 answer